ANALISIS PENDAPATAN PETANI USAHATANI MANGGIS DI DESA SIMPANG SUGIRAN KECAMATAN GUGUAK KABUPATEN LIMAPULUH KOTA - Miftahul Fadhilah; Dini Rochdiani (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Mangosteen are one of commodities cultivited in Simpang Sugiran Village. The problem faced by farmers in Simpang Sugiran Village are the use of ineffeictient production factors and delay in mangosteen exports due to Covid-19, which cause a decrease in income for mangosteen farmers. The purpose of this study is to analyze the farm income of mangosteen in Simpang Sugiran Village. The design in this study used a quantitative design and survey twchniques research methods.The Result of income analysis obtained by mangosteen farmer in Simpang Sugiran Village Rp. 1.508.207 per tree,  while the result of the R/C show a value of 5,92, which means that mangosteen farming is profitable.